(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Measuring the adequacy of mark technique is a troublesomeerrand. This paper analyzes the methodology to estimation of technique throughprovision of mark score and mark value as an instrument. The study was finishedin two stages. In the first stage mark score was computed by 150 post graduateadministration scholars. The second stage of the study was to compute mark valueutilizing the same respondents for the same marks. Top three marks innourishment, cool drink and telecommunication administration supplier portionswere chosen for the study. Higher Mcdonald’s mark score additionally had highermark value list when contrasted with Domino and Pizza cabin. It denotestechnique is working well as reflected in two measurable apparatuses. Singlesegment study for investigating the mark score and mark value record can giveknowledge into effect of procedure on the aforementioned two measurablemethodologies of procedure. It can additionally assists in decreasing wastageof promotional use. This could give an extent of further research because of lesswork done around there.